2019
DOI: 10.1111/aos.14152
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for Descemet membrane endothelial keratoplasty performed by two experienced corneal surgeons: a consecutive series of 40 cases

Abstract: Purpose: To describe the learning curve for Descemet's membrane endothelial keratoplasty (DMEK) in the Rotterdam Eye Hospital and to evaluate safety and visual outcome. Methods: This was a single-centre prospective study of 40 consecutive patients with Fuchs' endothelial dystrophy who underwent a DMEK procedure in the Rotterdam Eye Hospital. The performance of two corneal surgeons, each conducting their first series of 20 procedures, was examined with the cumulative summation test for the learning curve (LC-CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…CUSUM is a statistical tool, which is increasingly used to objectively evaluate the learning curves of surgical techniques [11][12][13][14][15][16][17][18][19][20][21]. It enables us to quantitatively compare two surgical methods (in this case, ELA vs. MMCR) using statistical process control method depending on consecutive operations [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CUSUM is a statistical tool, which is increasingly used to objectively evaluate the learning curves of surgical techniques [11][12][13][14][15][16][17][18][19][20][21]. It enables us to quantitatively compare two surgical methods (in this case, ELA vs. MMCR) using statistical process control method depending on consecutive operations [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, more objective analytic methods are required when comparing two different surgical techniques. Therefore, the cumulative sum (CUSUM) analysis has been developed to assess the learning curves of surgical procedures and is accepted in ophthalmology and many surgical fields [11][12][13][14][15][16][17]. CUSUM analysis, which is a statistical process control method, provides an objective and quantitative evaluation of surgical learning curves [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…After excluding 96 ineligible studies, 36 studies ( n = 11,401 eyes) were included in this systematic review. These included 17 non-randomized studies comparing DMEK alone to “triple DMEK” ( n = 8,304 eyes) with a mean follow-up duration of 12.8 ± 15.9 months (ranged, 6–60 months) ( 21 , 22 , 34 48 ), 14 studies on DMEK ( n = 2,609 eyes) with a mean follow-up duration of 20.0 ± 21.9 months (ranged, 3–42 months) ( 49 62 ), and five studies on “triple DMEK” ( n = 495 eyes) with a mean follow-up duration of 8.0 ± 3.4 months (ranged, 6–12 months) ( 63 67 ). Studies included were conducted at The Netherland (12 studies), Germany (nine studies), United States of America (seven studies), Canada (two studies), Egypt (one study), France (one study), Italy (one study), Nepal (one study), Spain (one study), United Kingdom (one study), and a multicenter study (23 countries).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis demonstrated that there was no statistical difference between DMEK alone and “triple DMEK” in terms of postoperative re-bubbling rate (RD −0.06; 95% CI: −0.13 to 0.00; I 2 = 73%; p = 0.07; Figure 4A ). Based on the findings of non-comparative studies, the overall re-bubbling rate following DMEK was estimated at 3.9% (95% CI: 1.9–5.8; n = 950 eyes from five studies; Figure 4B ) ( 52 , 55 , 58 , 59 , 62 ). No relevant data was available from “triple DMEK” studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation